Fusion of thermal and three-dimensional data for chronic wound monitoring - Gutierrez Ayala, Evelyn Patricia (2023)
Chronic wounds are a serious health problem because they do not follow a normal healing process and take a long time to heal. Monitoring the evolution of the wound is vital to evaluate the current treatment and determine the need for a different approach. Traditionally, this assessment is based on manual measurements and visual observation, which can be subjective and non-quantitative, leading to uncertainty in patient follow-up. This thesis proposes to leverage color and thermal imaging from cameras embedded in a smartphone to provide a non-invasive tool for wound assessment. Standard and affordable devices enables its applicability and scalability in clinical settings. We propose a methodology to create realistic and accurate 3D thermal models from a set of images captured with affordable and handheld devices. This approach was automated and evaluated in clinical settings on a total of 68 wound cases with varying degrees of severity, in Lima, Peru. Our findings show the feasibility of this method and highlight its potential for wound assessment through the use of thermal metrics derived from the 3D thermal models.